Perspective of healthcare professionals on barriers and facilitators in exploring end-of-life care preferences of patients with pulmonary fibrosis: A qualitative study - Lian Trapman; Lea M Dijksman; Jan C. Grutters; Saskia C.C.M. Teunissen; Everlien de Graaf (PLoS ONE, 2025)
Background Progressive pulmonary fibrosis is a lethal disease with a survival of 3–5 years with optimal medication treatment. Palliative care and advance care planning are therefore receiving increasing attention in the literature. However, structural implementation in clinical practice is still lacking. The aim of this study was to explore the needs, facilitators, and barriers for communication on the topic of end-of-life preferences of patients from the perspective of healthcare professionals. Methods A generic qualitative study was performed with focus groups and individual semi structured interviews with healthcare professionals. Data collection and analysis were performed iteratively. A thematic analysis was performed, following the methods of Braun and Clarke. Results Three focus groups and seven individual semi-structured interviews were conducted. Three themes were generated: (1) a lack of vision on palliative care, resulting in different approaches within the same clinic and showing the need for optimization of collaboration; (2) the importance of a learning-driven environment to support healthcare professionals skills and knowledge; and (3), the central role of the individual professional in developing skills and knowledge. Conclusions/discussion This study underscores the importance of behavioral and organizational change in palliative care to optimize conversations exploring values, preferences, and needs for end-of-life care for patients with pulmonary fibrosis. Leveraging the shared motivation of healthcare professionals to provide optimal care, integrating these findings into training and coaching programs can further enhance patient-centered approach in palliative care.